Satisfaction with the support received by parents of children with disabilities and the diversity of parental behaviour towards the child - Kuracki, Kamil (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Kamil Kuracki, Satisfaction with the support received by parents of children with disabilities and the diversity of parental behaviour towards the child. Interdisciplinary Contexts of Special Pedagogy, no. 26, Poznań 2019. Pp. 191–215. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.26.09 Raising, caring and rehabilitation of children with disabilities and developmental disorders is a serious challenge for their parents, because everyday situations associated with fulfilling parental duties generate a lot of various stress factors. Hence, receiving various kinds of social support seems to be an important factor affecting the well-being of parents. Thanks to this form of aid, it is possible to deal with a difficult situation and to reduce the disorder in family life. Moreover, the received support can significantly affect the parent-child relationship. This is particularly important in the context of reducing unfavourable behaviour and to intensify constructive parenting behaviour. The main aim of the study was to recognise the type of aid provided to parents of disabled children and to determine the relationship between the support received by parents and the development of the parent-child relationship. The research group consisted of 66 parents of preschool children with disabilities and 40 parents of children without disabilities. The tools used in the research were: the Parent Behavior Inventory by M.C. Lovejoy, R. Weis, E. O’Hare & E.C. Rubin, the Parent Cognition Scale by J.D. Snarr, A.M.S. Slep & V.P. Grande and the Parents’ Questionnaire by Agnieszka Dłużniewska. The study was conducted according to the correlation model